2018
DOI: 10.1007/s12032-018-1166-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of elderly gastric cancer patients after surgery: a nomogram to predict survival

Abstract: This study aimed to identify clinicopathological factors associated with the outcome of elderly patients with gastric cancer (GC), and to construct a nomogram for individual risk prediction. Tumor characteristics of 143 patients aged ≥ 80 years underwent surgery for GC were collected and analyzed by uni- and multivariate analyses. A prognostic nomogram was constructed using the factors which resulted to be significantly associated with overall survival. Discrimination of nomogram was tested by Kaplan-Meier (KM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…A foregoing study by Li et al showed that BMI, tumor site, T stage and N stage were connected with the OS of GC patients who received neoadjuvant chemotherapy [16]. Roberto et al reported that age, T stage, N stage, tumor residual after surgery, and pre-operatory ECOG-PS (performance status of Eastern Cooperative Oncology Group) were risk factors for prognosis of elderly GC patients after surgery; in addition, GC patients undergoing surgery perform0ed better survival results [17]. Most studies was 0.643 (95% CI, 0.608 to 0.678), there was a signi cant difference in two sets (p < 0.01); Secondly, high AUCs were noted in both development and validation sets (Figure.2); Thirdly, the nomogram calibration plot demonstrated high consistency between nomogram-predicted probabilities and actual outcomes for 3-and 5-year survival both in the development and validation sets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A foregoing study by Li et al showed that BMI, tumor site, T stage and N stage were connected with the OS of GC patients who received neoadjuvant chemotherapy [16]. Roberto et al reported that age, T stage, N stage, tumor residual after surgery, and pre-operatory ECOG-PS (performance status of Eastern Cooperative Oncology Group) were risk factors for prognosis of elderly GC patients after surgery; in addition, GC patients undergoing surgery perform0ed better survival results [17]. Most studies was 0.643 (95% CI, 0.608 to 0.678), there was a signi cant difference in two sets (p < 0.01); Secondly, high AUCs were noted in both development and validation sets (Figure.2); Thirdly, the nomogram calibration plot demonstrated high consistency between nomogram-predicted probabilities and actual outcomes for 3-and 5-year survival both in the development and validation sets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that a nomogram is superior to the AJCC TNM staging system in predicting the survival of cancer patients [14][15][16][17]. However, few studies have used nomograms to predict the prognosis of patients with small-intestine adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms have been widely used as a valuable pictorial tool for combining biological and clinical variables in the construction of prognostic models using traditional statistical methods such as a Cox proportional-hazards regression model to determine the prognosis of multiple malignancies [8][9][10]. In addition, several studies have shown that a nomogram is superior to the AJCC TNM staging system in predicting the survival of cancer patients [11][12][13][14]. However, few studies have used nomograms to predict the prognosis of patients with small-intestine adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%